Hepatitis B in sub-Saharan Africa: strategies to achieve the 2030 elimination targets. (December 2017) - Spearman, C Wendy; Afihene, Mary; Ally, Reidwaan; Apica, Betty; Awuku, Yaw; Cunha, Lina; Dusheiko, Geoffrey; Gogela, Neliswa; Kassianides, Chris; Kew, Michael; Lam, Philip; Lesi, Olufunmilayo; et al.
Summary: The WHO global health sector strategy on viral hepatitis, created in May, 2016, aims to achieve a 90% reduction in new cases of chronic hepatitis B and C and a 65% reduction in mortality due to hepatitis B and C by 2030. Hepatitis B virus (HBV) is endemic in sub-Saharan Africa, and despite the introduction of universal hepatitis B vaccination and effective antiviral therapy, the estimated overall seroprevalence of hepatitis B surface antigen remains high at 6·1% (95% uncertainty interval 4·6–8·5). In this Series paper, we have reviewed the literature to examine the epidemiology, burden of liver disease, and elimination strategies of hepatitis B in sub-Saharan Africa. This paper reflects a supranational perspective of sub-Saharan Africa, and recommends several priority elimination strategies that address the need both to prevent new infections and to diagnose and treat chronic infections. The key to achieving these elimination goals in sub-Saharan Africa is the effective prevention of new infections via universal implementation of the HBV birth-dose vaccine, full vaccine coverage, access to affordable diagnostics to identify HBV-infected individuals, and to enable linkage to care and antiviral therapy.